Education to transform people in the world, geography to change the world of people: theoretical approaches between Paulo Freire and Milton Santos - Nascimento, Júlio César Dias; Albuquerque, Enderson Alceu Alves (Geosaberes, 2017)
This article aims to expose the symmetries of thoughts in the works of two of the greatest Brazilian intellectuals: Paulo Freire and Milton Santos. Both authors play a notable role in their intellectual area, both nationally and internationally. Paulo Freire is the second Brazilian with more doctoral titles honoris causa. Milton Santos is the only Latin American winner of the Vautrin Lud Award, the equivalent of the Nobel Prize in Geography. The demand of the poorest has always been at the heart of the production of these authors, whether they are oppressed in Freirean reading, or non-citizens by the Miltonian perspective. In this perspective, this article is inserted in order to bring the geography of Milton Santos to the pedagogy of Paulo Freire in his efforts to build a different world, without oppressed and citizens, in fact.
Keywords: Paulo Freire; Milton Santos; Transformação.